Expression cloning of the Golgi CMP-sialic acid transporter. - Eckhardt, M (1996)
Translocation of nucleotide sugars across the membrane of the Golgi apparatus is a prerequisite for the synthesis of complex carbohydrate structures. While specific transport systems for different nucleotide sugars have been identified biochemically in isolated microsomes and Golgi vesicles, none of these transport proteins has been characterized at the molecular level. Chinese hamster ovary (CHO) mutants of the complementation group Lec2 exhibit a strong reduction in sialylation of glycoproteins and glycolipids due to a defect in the CMP-sialic acid transport system. By complementation cloning in the mutant 6B2, belonging to the Lec2 complementation group, we were able to isolate a cDNA encoding the putative murine Golgi CMP-sialic acid transporter. The cloned cDNA encodes a highly hydrophobic, multiple membrane spanning protein of 36.4 kDa, with structural similarity to the recently cloned ammonium transporters. Transfection of a hemagglutinin-tagged fusion protein into the mutant 6B2 led to Golgi localization of the hemagglutinin epitope. Our results, together with the observation that the cloned gene shares structural similarities to other recently cloned transporter proteins, strongly suggest that the isolated cDNA encodes the CMP-sialic acid transporter.